Towards Developing a Disclosure Index for Malaysian Zakat Institutions - Sapingi, R.; Sheikh Obid, S. N.; Puat Nelson, S. (Universiti Sains Islam Malaysia, 2024)
In view of understanding zakat reporting practices, this paper aims to develop a Zakat Disclosure Index (ZkDI) for Zakat Institutions (ZIs) in Malaysia. This is due to the finding of previous studies that highlighted zakat payers’ dissatisfaction on the insufficient information especially on zakat distribution part. The paper uses holistic accountability concept as a conceptual lens in developing the index. In developing the index; this paper starts by reviewing past literature and conducting semistructured interviews with zakat payers and recipients. Which then, it is reconciled and validated by a panel of experts to obtain the final ZkDI. Based on the discussions with the respondents, the results indicated that the institutions shall give more emphasis especially on financial and non-financial categories in their reporting as to ensure accountability is discharged effectively and consequently the religious obligation is fulfilled. A suggestion that annual report of zakat institutions shall be disclosed to the public was another interesting findings revealed in this paper. Since the paper focuses solely in Malaysia, thus applicability of the ZkDI to other Muslim countries which have different laws and regulations needs to be further examined. For future research, there is a possibility that the index can be improved by inviting more respondents to participate and eventually a better disclosure index can be created.